Pengaruh bahasa kampanye terhadap sadar kebersihan perilaku masyarakat - Gusnawaty (Lembaga Penelitian, Universitas Hasanuddin, 1991)
Effect of using slogans to the awareness of the clean environment in Ujung Pandang, Sulawesi Selatan Province; research report.